Characterizing Jordan Higher Centralizers on Triangular Rings through Zero Product - Majeed, A.H.; C.Shaheen, Rajaa (Iraqi Journal of Science, 2023)
n this paper , we prove that if T is a 2-torsion free triangular ring and be a family of additive mapping then satisfying is a higher centralizer which is means that is Jordan higher centralizer on 2-torsion free triangular ring if and only if is a higher centralizer and also we prove that if be a family of additive mapping satisfying the relation Σ , Then is a higher centralizer.